Total Sportscasting - Zumoff, Marc; Negin, Max (Routledge, 2014)
Whether you want to be in front of the camera, on the microphone, or behind the scenes, Total Sportscasting gives you the skills you'll need to become successful in this dynamic industry. This book covers everything from performance and production techniques to all aspects of sportscasting, good broadcast writing techniques, and how best to forge lasting relationships with team personnel. It also delves into the unique issues facing women sportscasters. And when it comes to breaking into the business, Total Sportscasting devotes entire chapters to career development and demo reel production. For important perspective, we've also included chapters on the history of sportscasting and attempts to glimpse into its future. Total Sportscasting is packed with a variety of features for both learning and instructing: Complete coverage of every aspect of the sportscast, helping you prepare for any platform-TV, radio, and the web Interviews with successful sports journalists, producers, and directors who give you an inside look into the real-world practices of the industry A companion website, which provides additional resources for both instructors and students, including video and audio examples and links to additional resources: www.totalsportscasting.com.